The Effect Of Gear Ratio Variations And Vehicle Weight On Energy Efficiency In Electric Prototype Vehicles Of The Engineering Faculty Of Mataram University - Bima, Rangga; Mara, I Made (ROTASI, 2025)
Electric vehicles are vehicles that are driven by electric motors using electrical energy derived from battery energy sources. Like most other electric vehicles, electric prototype vehicles are also controlled using throttle pedals on the steering wheel and also the braking system. This study also aims to determine how much electrical energy consumption is used in the vehicle, by varying the gear ratio and vehicle weight. The test method was carried out by releasing the throttle when the vehicle reached maximum speed, with the aim of being able to produce a lower level of energy consumption with higher efficiency. Gear ratio variations used were 6.43; 7.56; 8.57; 9.08 and 10.20 and vehicle weight variations used were 120.5 kg; 130.5 kg and 140.5 kg. The results of the test show that if the smaller the gear ratio used and the heavier the load from the vehicle, the greater the energy required. The results of this study indicate that, vehicles with lighter weight and with the use of larger gear ratio variations can reduce the consumption of electrical energy used. And can increase higher energy efficiency, so as to increase the maximum mileage range of the vehicle. The findings from this study can also provide additional information and valuable insights in the development of more efficient electric vehicles in the future.